Analisis Multidimensional Kepatuhan Pajak UMKM Di Kabupaten Karanganyar : Pemahaman, Kesadaran, Love Of Money Dan Kondisi Keuangan : Studi Empiris Di Kabupaten Karanganyar - Ani, Ani; Harimurti, Fadjar (Politeknik Negeri Ambon, 2025)
This research examines the multidimensional analysis of understanding, awareness, love of money, and financial conditions concerning the tax compliance of MSMEs in Karanganyar Regency. This research uses micro-scale MSME objects in Karanganyar Regency. The research method used is a quantitative method using SPSS version 27.0 to analyze the data. The data sources used in this research are primary data and secondary data. The population in this study consists of 39,908 individual taxpayers of micro-scale SMEs registered with the Cooperative, Small, and Medium Enterprises Office of Karanganyar Regency. The sample in this study was determined using the Slovin formula, resulting in 100 MSMEs. This study uses the cluster random sampling method. The data collection techniques used in this research are questionnaires, observations, and literature studies. The data analysis technique used is multiple linear regression. The research results show that tax understanding does not significantly affect the tax compliance of MSMEs in Karanganyar Regency. Meanwhile, tax awareness, love of money, and financial condition positively and significantly impact the tax compliance of SMEs in Karanganyar Regency.